Economic and Social Development of Bangladesh Miracle and Challenges (Springer International Publishing, 2018)
This book discusses Bangladesh's economic and social development that may be called a "miracle" since the country has achieved remarkable development progress under several unfavorable situations: weak governance and political instabilities, inequality, risks entailed in rapid urbanization, and exposure to severe disaster risks. The authors examine what led to this successful economic development, and the potential challenges that it presents, aiming to elicit effective policy interventions that can be adapted by other developing countries.